2011
DOI: 10.1111/j.1365-2265.2010.03911.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional analysis of novel human growth hormone-releasing hormone receptor (GHRHR) gene mutations in Japanese subjects with short stature

Abstract: The homozygous GHRHR mutation was rare, being detected in only one Japanese IGHD family. Future research is needed to clarify the genetic contributions of heterozygous functional promoter variants to GHD, ISS and normal-stature variations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
1
20
0
2
Order By: Relevance
“…On the other hand, our observations are consistent with those in Ghsr -/-mice supporting that ghrelin-GHSR signal is not a key contributor to somatic growth in rodents (10). In contrast, several genetic studies support the role of GHSR as a physiological contributor in humans both to the adult height variance among individuals (23)(24)(25) and to the nosology of somatic growth disorders (22,45,46).…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, our observations are consistent with those in Ghsr -/-mice supporting that ghrelin-GHSR signal is not a key contributor to somatic growth in rodents (10). In contrast, several genetic studies support the role of GHSR as a physiological contributor in humans both to the adult height variance among individuals (23)(24)(25) and to the nosology of somatic growth disorders (22,45,46).…”
Section: Discussionsupporting
confidence: 87%
“…c.1146G>A is located in the last nucleotide of exon 12, immediately upstream of the splice donor site. This mutation was previously reported [12]. Although it does not predict change of amino acids, in vitro splicing studies showed skipping of exon 12 [12].…”
Section: Resultsmentioning
confidence: 94%
“…Patient 3 and her parents were evaluated, and these results compared with previously published data from Japanese c.1146G>A mutated patients [12]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GHRH-R mutations were not observed or were rare in several other populations. Mutations were not found among Dutch and Argentinean children with IGHD and were found only in three out of a cohort of 127 Japanese children, 14 with IGHD and 113 with idiopathic short stature [14][15][16]. Thus the lower prevalence of GHRH-R codon 72 mutation observed by us is not unexpected.…”
Section: Age Groups (Years) ≤5mentioning
confidence: 64%